Crystal structure of dimethyl (1α,2β,3α,4β,7β,8α,9β,10α) -13-di(methylthio)methylidene-pentacyclo[8.2.1.14,7.0 2,9.03,8]tetradeca-5,11-diene-2,9-dicarboxylate, C 21H24O4S2 - Palmer, C. (2014)
Zeitschrift fur Kristallographie - New Crystal Structures